Aggressive debridement and early antifungal therapy in the management of cutaneous mucormycosis: A case report with review of literature (Indian Journal of Case Reports, 2024)
Mucormycosis is an infectious disease caused by fungi. The worldwide spread of coronavirus disease-19 did create a public health crisis, infecting millions of people and causing huge numbers of deaths worldwide. Cutaneous manifestations of mucormycosis can either be primary or secondary diseases. Clinical manifestations can vary from cellulitis, abscess, or ulcer. Standard management includes early diagnosis, surgical debridement, and antifungal therapy. Early initiation of antifungal therapy can lower mortality rates and improve the prognosis of patients. The estimated mortality ranges from 25% to 87%, depending on the site of infection.